2014
DOI: 10.1111/1749-4877.12088
|View full text |Cite
|
Sign up to set email alerts
|

Paleontology and evolution–part I

Abstract: ogy and Evolutionary Biology appear mutually interrelated disciplines where the fossil record can both notably constrain the evolutionary history of the biosphere in a deep time perspective, and provide valuable hints to forecasting the direction of future evolutionary scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In a recent paper published in a special issue of Integrative Zoology on ‘Paleontology and evolution–part I.’ (Palombo ), the author (van der Geer ) takes a review of the derived traits observed in endemic fossil insular mammals, including body size variation, cranial and postcranial changes, and modifications in dentition. At one point in the discussion, the author misinterprets and seriously distorts statements by Jordana et al () on the relationship between hypsodonty and longevity in the fossil insular bovid Myotragus balearicus Bate, .…”
mentioning
confidence: 99%
“…In a recent paper published in a special issue of Integrative Zoology on ‘Paleontology and evolution–part I.’ (Palombo ), the author (van der Geer ) takes a review of the derived traits observed in endemic fossil insular mammals, including body size variation, cranial and postcranial changes, and modifications in dentition. At one point in the discussion, the author misinterprets and seriously distorts statements by Jordana et al () on the relationship between hypsodonty and longevity in the fossil insular bovid Myotragus balearicus Bate, .…”
mentioning
confidence: 99%